Solving a Traffic Congestion Problem at T-intersections using AnyLogic Simulation - Kazmi, Syed Muhammad Mustafa; Sun, Xu; Yu, Hao; Pettersen, Jan-Arne; Thordarson, Diana Santalova (FRUCT, 2022)
Source at: https://fruct.org/publications/volume-32/acm32/ Beyond its significance in urban planning and traffic engineering, the optimal design of road networks is crucial for the uninterrupted flow of traffic. Traffic congestion results in increased travel times and waiting times as well as higher CO 2 emissions. It is therefore imperative to study and optimize the traffic flow through roads and junctions to avoid such conditions. In this paper, a highly congested T-intersection in Narvik, Norway, is analyzed and several alternative plans are tested to reduce the travel time through the junction and the waiting time for cars in queues. The process begins with the collection of traffic data to estimate the current waiting times and understand the queuing problem. The current state is modeled in AnyLogic to simulate the actual conditions at the intersection. Two alternate solutions are then presented and analyzed. One is the use of traffic lights, and the other is the installation of a roundabout. The waiting times and queues associated with the two alternatives are compared with the current state to determine the better alternative. This paper presents the effectiveness of using simulation to solve the traffic congestion problems at T-junctions, and the method can be applied to various similar problems.